Zimbabwe under colonial rule, in Government reports, 1897-1980. - Great Britain. Foreign and Commonwealth Office (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2015)
The occupation of Southern Rhodesia was first triggered by the discovery of gold in South Africa. When the British South Africa Company's hopes of uncovering gold in Mashonaland were not realised, they attacked and defeated the Ndebele in 1893, then occupied Matabeleland too. The Company's treatment of the native population inspired the Shona and Ndebele Risings of 1896-1897, this rebellion was defeated with great difficulty. After its defeat some more experienced colonial managers were appointed to administrate Rhodesia and those managers initiated the publication of the reports reproduced here. Southern Rhodesia was first formally annexed as a British colony from 1923, Northern Rhodesia became a British Colony in 1924. From 1953 to 1963 Southern Rhodesia was re-united with Northern Rhodesia to form the Federation of Rhodesia and Nyasaland. The Federal period witnessed considerable white immigration, the white population of Southern Rhodesia trebled between 1945 and 1960;" this increase was actively encouraged by the white population who administered the running of the country. This exponential population growth increased political tensions between the native and the white populations, these tensions came to a head in the mid 1960?s. In 1964 Northern Rhodesia became independent as Zambia, Southern Rhodesia would begin calling itself Rhodesia. Then in 1965, after its attempts to negotiate independence failed, the government which only represented the white settlers made a Unilateral Declaration of Independence. This declaration of 'independence' was not recognised by the outside world and gave rise to guerrilla warfare internally. The war ended with a 'power-sharing' agreement including some black politicians in June 1979;" this was followed by the constitutional agreement between the warring factions of Zimbabwe and the UK Government, which was reached at Lancaster House in December 1979, this in-turn led to the first election under universal suffrage. These annual reports illustrate the dramatic historical development of Southern Rhodesia from corporate colonisation, through imperial colonisation, to independence.
Date range: 1897-1980.
Keywords: Zimbabwe -- Politics and government -- 1890-1965.